Jane Austen Pride And Prejudice - Austen, Jane; Jane Austen 1775-1817 (London Harper Collins, 2010)
"Darcy had never been so bewitched by any woman as he was by her." With all the forces of the world conspiring to keep Mr. Darcy and Elizabeth Bennet apart, how will fate manage to bring them together? It certainly won't be easy if they're fighting it every step of the way. But theirs is a love that was meant to be, despite all the odds against them. One of the most captivating love stories of all time, Jane Austen's enduring masterpiece is beloved by generation after generation. Beautifully presented for a modern teen audience, this is the must-have edition of a timeless classic.
Keywords: Socila Classes -- England- Fiction -- Manner and Customs -- Courtship- Fiction